Erectile Dysfunction: Pharmacological Pathways with Understudied Potentials - Doaa R. Adam; Manal M. Alem (Biomedicines, 2022)
Erectile dysfunction (ED) is a public health concern worldwide. In the past, it was perceived as a phenomenon attributed to age advancement. However, more individuals are affected every year that do not fall under that age criterion. Epidemiological research revealed that this abnormality has an association with endothelial dysfunction connected to several cardiovascular (CV) risk factors. Currently, ED is interpreted as a clinical marker for future adverse events and not only as a present health issue that negatively affects the quality of life. The management of ED involves lifestyle modifications, therapeutic optimization for comorbid conditions, and pharmacological and psychosexual therapy. Phosphodiesterase type 5 (PDE5) inhibitors are the first-line pharmacological agents to be prescribed for such a condition. Nonetheless, other pharmacological pathways and agents remain underinvestigated or were investigated at some stage. This review aimed to present to future researchers interested in this field with some pharmacological agents that showed favorable effects on a limited number of studies on human subjects or experimental models.